Toward a framework for best practices and research guidelines for perinatal depression research. Issue 7 (28th March 2019) - Kimmel, Mary C.; Bauer, Anna; Meltzer‐Brody, Samantha
Abstract: This review article highlights the current state of perinatal depression (PND) research including established standards of care and innovative research in progress. PND can have a significant adverse impact on mother, child, and family; however, to date, wide‐scale identification, prevention, and treatment have been limited. PND is heterogenous in presentation with likely multifactorial etiologies for each woman. Challenges in PND research are discussed including a need for universal tools, standardized measures, benchmarks, and best practices. Current examples are reviewed that highlight approaches to novel treatment paradigms and interventions. This includes reviewing epidemiologic studies in PND research, examining the biological underpinnings of PND, and discussing examples from this field and other fields currently developing translational research that spans from bench to bedside. Current and future challenges and opportunities in developing best practices for the treatment of PND are outlined. We also discuss the use of the NIMH Research Domain Criteria approach for PND research and provide recommendations for future directions in PND research collaboration. In conclusion, greater precision in perinatal psychiatry can be possible in the future with the development of guidelines and best practices that build on current work and apply innovative and collaborative approaches of scientists, providers, patients, community members, and government officials.